Allelic expression of AhNSP2-B07 due to parent of origin affects peanut nodulation - Zhao, Zifan; Wang, Yichun; Peng, Ze; Luo, Ziliang; Zhao, Meixia; Wang, Jianping (Frontiers in Plant Science, 2023)
Legumes are well-known for establishing a symbiotic relationship with rhizobia to fix nitrogen from the atmosphere. The nodulation signaling pathway 2 (NSP2) gene plays a critical role in the symbiotic signaling pathway. In cultivated peanut, an allotetraploid (2n = 4x = 40, AABB) legume, natural polymorphisms in a pair of NSP2 homoeologs (Na and Nb) located on chromosomes A08 and B07, respectively, can cause loss of nodulation. Interestingly, some Nbnb heterozygous progeny produced nodules (Nod+) while some others do not (Nod–).¬ In this study, we detect the allelic expression at the Nb locus. Previous reciprocal crosses between nanaNbNb and nananbnb plants showed that F1 hybrids (nanaNbnb), which inherited the Nb allele only from female parents showed Nod– phenotype, which led to the hypothesis that the gene expression of AhNSP2-B07 in female gametes is inhibited in F1 plants. qRT-PCR experiments revealed that the expression of AhNSP2-B07 in the ovary was significantly lower than that in pollen, regardless of genotypes or phenotypes, indicating that expression of AhNSP2-B07 gene in peanut depends on the parent of origin and is female imprinted. To investigate whether the female imprinting is caused by DNA methylation, we compared the methylation levels of Nb between the ovary and pollen. No significant differences in methylation were detected between these two tissues, suggesting that the differential expression of Nb between male and female gametes is not caused by the methylation level. Our study provided a unique genetic basis of a key gene involved in peanut symbiosis, which could facilitate understanding the regulation of gene expression in symbiosis in polyploid legumes.